A Sandwich‐type Electrochemical Immunosensor for the Sensitive Determination of Salmonella Typhimurium in Food. Issue 5 (13th January 2022) - Sun, Qiaoling; Liu, Xiaojun; Tang, Haowen; Qian, Yuying; Gu, Haiying; He, Hong
Abstract: A sandwich‐type electrochemical immunosensor was developed for sensitive detection of Salmonella Typhimurium ( S . Typhimurium) in milk and eggs. According to the antigen‐antibody specific binding, Anti‐ S . Typhimurium antibody was used to recognize the S . Typhimurium, while the HRP‐Anti‐ S . Typhimurium antibody as signal probe was used to catalyze H2 O2 with the assistance of thionine. The immunosensor showed wide linear range from 5.6×10 1 to 5.6×10 8 CFU/mL and low detection limit of 35 CFU/mL. The immunosensor also exhibited excellent specificity, reproducibility and stability, indicating that it had practicability in quality control of complex food samples and potential in clinical applications. Abstract :